Comparison of the Efficacy of Selected Bacterins against Edwardsiella Tarda in Immunized Japanese eel (Anguilla japonica) (Bangladesh Journal of Microbiology, 2016)
An effective vaccine against Edwardsiella tarda has not been reported in substitution for high concentration of formalin for the prevention of edwardsiellosis disease. In this study, the efficacy of inactivated E. tarda was evaluated and compared by intraperitoneal (IP) injection-immunization or challenge against Japanese eel (Anguilla japonica). Formalin, formalin with heat, citric acid, pressure and electric current were used for inactivation of the bacteria, and the relative percent survival (RPS) values of pressure (600 psi for 5 min) killed cells was determined. PKCinactivated vaccine showed 89-93% protection that was higher than others. PKC-inactivated vaccine at a concentration of 106 cells/fish was sufficient to induce high protection (RPS>89). Protection of the different-inactivated vaccines was evaluated at different time post immunization, and the peak of protection was observed at 9 days post-challenge. Fish immunized with PKC showed significantly (P